Enhancing English Vocabulary Using Story-Based Vocabulary Game of Grade Eight Students - Maria Kandida Kardoso; Jamiluddin Jamiluddin; Grace Novenasari Manurung; Aminah Suriaman (Journal of English Language and Education, 2026)
This study examined the impact of Story-Based Vocabulary Game on English vocabulary mastery of grade eight students at SMP Kristen Bala Keselamatan Palu. This study employed a quantitative approach with a quasi-experimental design. Pre-test and post-test were administered to measure students’ vocabulary mastery before and after the treatment. The findings showed that the students’ vocabulary mastery improved after the implementation of the treatment. The collected data were analyzed statistically to determine whether there was a significant difference between the experimental group and the control group. The results indicated that the average post-test score of experimental groups (56.52) was higher than the control group (42.37). In addition, based on the hypothesis analysis, it showed that the t-test the t-table (2.032 2.008), indicating that the research hypothesis is accepted. Therefore, it can be concluded that the Story-Based Vocabulary Game media significantly improves students’ vocabulary mastery.